EFFECT OF MASS TRANSFER ON THE KINETICS OF MICROBIOLOGICAL SYNTHESIS - Obodovich А.; Podobiy Е.; Sidorenko, V. (Energy and Automation, 2016)
The paper analyzes the features of mass transfer of oxygen into the culture fluid in the process of growing the fodder yeast.